Molecular marker analysis and interval mapping of QTL for root and shoot traits in the Danteshwari/ Dagad Deshi RIL population of rice (Oryza sativa L.) - Sinha, Sweta; Kotasthane, A S; Verulkar, S B (ORYZA-An International Journal of Rice, 2018)
Nine hundred and thirty seven (788 HvSSR, 108 RM, 5 RGNMS and 36 SNP) markers were surveyed for parental polymorphism between indica cultivars Danteshwari and Dagad Deshi. One hundred and four (11.9 %) markers exhibited polymorphisms which were further analyzed for marker segregation on F7 275 RILs. Thirty eight (36.54%) markers showed expected 1:1 segregation and rest 63.46 % of the markers showed distorted segregation. Linkage map was constructed, using 104 (SSR and SNP) markers across the 12 rice chromosome covering 2665.5 cM in length. Interval mapping analysis identified 12 putative QTLs for root and shoots traits explaining phenotypic variability from 4.41% to 27.49%. For total plant length, 5 putative QTLs were identified on chromosomes 1 and 4. Three putative QTLs for shoot length were detected on chromosome 1. Out of 2 putative QTLs for shoot dry weight, 1 was located on chromosome 5 and another on chromosome 10. Whereas single putative QTL for shoot fresh weight and root volume was positioned on chromosome 5 and 6, respectively. The result also suggests that the different analysis model played a role in detection of QTLs. Further, the identified QTLs may be used in rice breeding programme for the improvement in the root and shoot traits.